Mycobacterium tuberculosis persistence mutants identified by screening in isoniazid-treated mice - Dhar, Neeraj (National Academy of Sciences, 2010)
Tuberculosis (TB) is notoriously difficult to cure, requiring administration of multiple antibiotics for 6 mo or longer. Conventional anti-TB drugs inhibit biosynthetic processes involved in cell growth and division, such as DNA replication, RNA transcription, protein translation, and cell wall biogenesis. Although highly effective against bacteria cultured in vitro under optimal growth conditions, these antibiotics are less effective against bacteria grown in vivo in the tissues of a mammalian host. The factors that contribute to the antibiotic tolerance of bacteria grown in vivo are unknown, although altered metabolism and sluggish growth are hypothesized to play a role. To address this question, we identified mutations in Mycobacterium tuberculosis that impaired or enhanced persistence in mice treated with isoniazid (INH), a front-line anti-TB drug. Disruption of cydC, encoding a putative ATP-binding cassette transporter subunit, accelerated bacterial clearance in INH-treated mice without affecting growth or survival in untreated mice. Conversely, transposon insertions within the rv0096–rv0101 gene cluster attenuated bacterial growth and survival in untreated mice but paradoxically prevented INH-mediated killing of bacteria in treated mice. These contrasting phenotypes were dependent on the interaction of the bacteria with the tissue environment because both mutants responded normally to INH when grown in macrophages ex vivo or in axenic cultures in vitro. Our findings have important implications because persistence-impairing mutations would be missed by conventional genetic screens to identify candidate drug targets. Conversely, persistence-enhancing mutations would be missed by standard diagnostic methods, which are performed on bacteria grown in vitro, to detect drug resistance.